Correlates of walking among disadvantaged groups: A systematic review. (May 2020) - Hilland, Toni A.; Bourke, Matthew; Wiesner, Glen; Garcia Bengoechea, Enrique; Parker, Alexandra G.; Pascoe, Michaela; Craike, Melinda
Abstract: Socioeconomically disadvantaged groups are less likely to be physically active. Walking is important to public health, therefore understanding correlates of walking will inform the development of targeted interventions. The aim of this systematic review was to examine the correlates of walking among socioeconomically disadvantaged adults. PubMed/MEDLINE and Scopus were searched up to February 2020 and titles/abstracts and full-texts were screened against eligibility criteria. Methodological quality was assessed. Correlates were synthesized when two or more comparisons were available. 35 studies were selected for synthesis. 21 examined overall walking, 16 examined leisure-time walking and 9 examined walking for transport (8 examined two or more types of walking). Employment status, home ownership, self-rated health, density or number of social ties, perceived neighborhood aesthetics, perceived walkability and perceived individual safety were positively associated with overall walking. Social support for physical activity from friends and family and perceived individual safety were positively associated with leisure-time walking. Objective walkability, perceived walkability and perceived individual safety were positively associated with walking for transport. Most studies were cross-sectional, did not report response rates and used a validated measure of physical activity. Strategies to improve self-rated health, social ties, neighborhood aesthetics, walkability and perceptions of individual safety should be the focus of interventions that aim to improve walking among socioeconomically disadvantaged groups. Recommendations for future studies include the need to focus on leisure-time walking and walking for transport; the correlates of walking in males; prospective longitudinal designs; psychological, cognitive and emotional variables; and social, behavioral attributes and skills. Highlights: The factors influencing the different types of walking behavior vary. Interventions should focus on improving self-rated health, social ties, aesthetics, walkability and individual safety. Future studies need to focus on psychological, social, cultural, behavioral attributes and skills.